Histopathology of intersymphyseal band and its correlation with continence in bladder exstrophy repair - Bharati K. Kulkarni; Nandita Saxena; Shyam S. Borwankar; Hemant N. Lahoti; Pooja Multani; Dipesh Goel (SpringerOpen, 2021)
Abstract Background Urinary incontinence is a major problem in operated exstrophy patients. Most of the repairs described in literature stress on the importance of dividing the intersymphyseal band (ISB) to place the bladder in the pelvis. But the origin of this band and its importance has hardly been discussed in literature. The purpose of this study is to establish the nature of tissue the ISB is composed of. This can be used to determine its role in the surgical management of exstrophy epispadias complex (EEC) patients. Results Thirty out of 33 operated patients demonstrated smooth muscle with/without fibrous tissue in the sections taken through the ISB. A significant percentage of patients (χ 2 = 38.319, p < 0.0001) in whom this band was reconstructed around the bladder neck gradually became continent/partly continent with an increase in the dry interval with time. Conclusion It can be a considerable factor to pay attention to the step of wrapping the ISB around the bladder neck during EEC repair. This serves to function as the smooth muscle of the bladder neck as proven histologically in our operated patients. It may have a role to support future continence in these patients.